Hemodialysis Adequacy and Its Impact on Long-Term Patient Survival in Demographically, Socially, and Culturally Homogeneous Patients - Reza Hekmat (International Journal of Nephrology)
Background. Impact of hemodialysis adequacy on patient survival is extensively studied. The current study compares the survival of chronic hemodialyzed, undocumented, uninsured, Afghan immigrant patients with that of a group of insured Iranian patients matched for underlying disease, age, weight, level of education, marital status, income, and number of comorbid conditions. Methods. Eighty chronic hemodialysis patients (mean age 42.8 ± 10.5 years) entered this historical cohort study in Mashhad, Iran, between January 2012 and January 2015. Half of the patients were undocumented, uninsured, Afghan immigrants (Group A) matched with forty insured Iranian patients (Group B). To compare the survival rate of the two patient groups, Kaplan–Meir survival analysis test was used. Results. Group A patients were underdialyzed with a weekly Kt/V which was significantly less in comparison with that of Group B (1.63 ± 0.63 versus 2.54 ± 0.12, p value = 0.01). While Group A’s number of hemodialysis sessions per week was fewer than that of Group B (1.45 ± 0.56 versus 2.8 ± 0.41, p value = 0.04), the mean of Kt/V in each hemodialysis session was higher in them, in comparison with Group B (1.43 ± 0.25 versus 1.3 ± 0.07, p value = 0.045). In Group B and Group A patients, one-year survival was 70% versus 50%, two-year survival was 55% versus 30%, and three-year survival was 40% versus 20%, respectively (p values = 0.04, 0.02 and 0.04, respectively). In Cox regression analysis, hemodialysis adequacy and uninsurance were factors impacting patients’ survival (OR = 1.193 and 0.333, respectively). Conclusions. Undocumented, uninsured, inadequately hemodialyzed, Afghan patients had a significantly lower one-, two-, and three-year survival as opposed to their Iranian counterparts, probably due to lack of insurance.